Loyalty in Business Banking - Fragata, Anabela (2017)
The main purpose of this investigation is to analyze the major determinants of loyalty, for the Portuguese business banking customers in the traditional bank branch and in online banking. The subject customer loyalty has been extensively explored in the marketing literature, especially for the private customers and small companies’ bank segments. Considerable discussion exists in the academic literature over the definition and dimensionality of loyalty. Many definitions are based in behavioral intentions (repurchase or purchase frequency), attitudinal (positive affect toward the relationship continuance), active loyalty (word of mouth and intention to use), passive loyalty (not switching under less positive conditions) and some authors propose a combination between these approaches. Numerous studies have also been conducted to identify the benefits that customer loyalty delivers to an organization. The majority of this research has concentrated on the financial benefits derived from retaining customers, including the initial cost of introducing and attracting new customers, increases in the number of purchases, and also a reduction in defection can contribute to an increase in profits far more than an increase in the market share. Loyalty in financial services has been viewed in relation to the length of time a customer has been with a provider, number of services used, and frequency of service use, customer´s recommendations, and customer´s price indifference, low likelihood of switching and high potential of increasing volume of product use.